Preliminary Investigation Of Using DBD Plasma For Application In Micro Combustors - Abdul Munir, Fudhail; Musthafah, Mohd Tahir; Mohd Ridzuan Tan, Nurfarah Diana; Saputro, Herman; Mikami, Masato (Penerbit Akademia Baru, 2021)
Dielectric-Barrier-Discharge (DBD) plasma actuators are one of the recent research topics that has caught worldwide attention. Plasma actuators are typically used in the aerospace field of study for their flow control and wide usage of different types of plasma actuators. DBD plasma actuator is an immobile actuator that able to be utilized for its flexibility and light weight parts. Due to the wide usage of DBD plasma, it is also able to be useful in the field of combustion in terms of air flow control. In this research, the DBD plasma actuator is tested on its ability to be applied in micro combustors based on the air flow controlling aspect, the temperature of plasma and effects of vibration of plasma. Experiments were performed in the wind tunnel with smoke generator to show the flow separation by DBD plasma actuator while infrared camera and accelerometer were used to sense the temperature and vibration respectively to investigate the effects of DBD plasma actuator on these aspects. Results shows that the plasma generated has minimal effects of the flow characteristics whereas the temperature of plasma has a maximum of 90?celcius when it is generated continuously. The vibration results indicate that generating plasma produces a small amount of vibration.